The effect of preoperative embolization rate on surgical outcomes for carotid paraganglioma resection - Yildirim, Mustafa; Yildirim, Hanefi; Dogan, Yusuf (Assoc Medica Brasileira, 2024)
OBJECTIVE: Preoperative embolization of paragangliomas decreases tumor volume and reduces intraoperative blood loss. This study aimed to evaluate the effect of the rate of devascularization achieved by preoperative embolization of carotid body tumors on surgical outcomes. METHODS: Patients with carotid body tumors who underwent preoperative transarterial embolization between 2013 and 2024 were included in this retrospective study. The Shamblin classification of all patients was carried out using radiological imaging. Devascularization rates obtained after the embolization of carotid body tumors were determined from angiographic images. Patients were divided into two groups: near-complete embolization (devascularization rate >90%) and incomplete embolization (devascularization rate <90%). Hemoglobin loss was calculated with blood tests before and immediately after surgery. Tumor volume loss was calculated by preoperative radiological tumor volume and postoperative surgical specimen volume. Hemoglobin loss, tumor volume loss, and postoperative complication rates of the two groups were compared. RESULTS: A total of 31 patients with carotid body tumors who underwent surgery were included in the study. Near-complete embolization was achieved in 21 patients (67.74%), while incomplete embolization was achieved in 10 patients (32.25%). Shamblin classification was statistically similar (p>0.05) between the two groups. The vascular complication rate in the near-complete embolization group was significantly lower than in the incomplete embolization group (p=0.027). However, no significant difference was observed in neurological complication rates, hemoglobin loss, and tumor volume loss parameters between the two groups (p>0.05). CONCLUSION: The preoperative devascularization rate should be at least 90% to minimize the risk of vascular complications.
Keywords: Carotid body tumor; Vascular complication; Artery embolization